Predictive Value of Echocardiographic Strain for Myocardial Fibrosis and Adverse Outcomes in Autoimmune Diseases - Jia, Fuwei; Li, Xiao; Zhang, Dingding; Jiang, Shu; Yin, Jie; Feng, Xiaojin; Zhu, Yanlin; Liu, Yingxian; Zhu, Yuanyuan; Lai, Jinzhi; Yang, Huaxia; Fang, Ligang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Myocardial fibrosis is an important pathophysiologic mechanism of cardiac involvement that leads to increased mortality in patients with autoimmune diseases (AIDs). The aim of this study was to evaluate the association between myocardial strain from speckle-tracking echocardiography (STE) and fibrosis on cardiovascular magnetic resonance (CMR) and to further explore their prognostic implications in patients with AIDs. Methods We prospectively included 102 AIDs patients with clinically suspected cardiac involvement and 102 age- and sex-matched healthy individuals. Patients underwent CMR for evaluation of myocardial fibrosis by late gadolinium enhancement (LGE) and T1 mapping. A semiquantitative evaluation based on the extent of LGE was used to calculate the total (tLGEs) and segmental (sLGEs) LGE score. Global longitudinal strain (GLS) was evaluated by STE in all subjects. All patients were regularly followed up every 6 months. The primary endpoint was the composite incidence of all-cause death and cardiovascular hospitalization. Results Compared to healthy controls, AIDs patients had impaired GLS (−17.9 ± 5.1% vs. −21.2 ± 2.5%, p < 0.001). LGE was detected in 70% of patients. Patients with LGE presented worse GLS (−17.1 ± 5.3% vs. −19.6 ± 4.1%, p = 0.018) than those without LGE. On multivariate logistic analysis, GLS ≥ −15% was an independent predictor of LGE presence (OR = 4.98, 95%CI 1.35–18.33, p = 0.016). Moreover, a marked and stepwise impairment of segmental longitudinal strain (−19.3 ± 6.6 vs. −14.9 ± 6.5 vs. −8.9 ± 6.3, p < 0.001) was observed as sLGEs increased. During a median follow-up time of 25 months, 6 patients died, and 14 patients were hospitalized for cardiovascular reasons. Both GLS ≥ −15% (HR 3.56, 95%CI 1.28–9.86, p = 0.015) and tLGEs ≥ 6 (HR 4.13, 95%CI 1.43–11.92, p = 0.009) were independently associated with the primary endpoint. Conclusions In AIDs patients, impaired myocardial strain on STE could reflect the presence and extent of myocardial fibrosis and provide incremental prognostic value in addition to LGE in the prediction of adverse outcomes.